MANUMBUAK PADI PADA KARYA SULAM - Maharani, Maharani; Widdiyanti, Widdiyanti; yulimarni, yulimarni (Institut Seni Indonesia Padangpanjang, 2024)
Manumbuak padi is an activity of Minangkabau`s women in processing paddy into rice traditionally using traditional tools. the traditional tools is lasuang, pestle/antan and tampian. Nowadays, rice processing using lasuang is starting to be abandoned, because it has been replaced by more sophisticated technology. This is the interest and concept in creating embroidery works. The embroidery creation methods that we used are three-stage theory, the exploration stage, looking for ideas and reference sources. The design stage, namely expressing ideas in the form of a design, continued with the realization stage. The work is made using embroidery techniques using cotton linen and polycherry thread. The works in the form of wall decorations have a diameter of 80 cm, and each work has a storyline according to its title, namely Work 1 entitled manjamua padi (drying rice), work 2 manumbuak padi (pounding rice), work 3 basumarak (lively/excited), work 4 manampi (winnowing), work 5 manyumpik bareh (putting rice into a sack), and work 6 malapeh panek (unwinding or resting).